Production process of high-strength anti-distortion cold-rolled strip steel
By using medium carbon steel with specific compositions, gradient quenching-isothermal tempering process, and nano-ceramic composite coating technology, the problems of balancing strength and toughness and insufficient surface properties of cold-rolled strip steel have been solved, enabling the production of high-strength, low-distortion, and corrosion-resistant cold-rolled strip steel.
Patent Information
- Application Number
- CN202511061781.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-31
- Publication Date
- 2025-11-28
AI Technical Summary
While traditional cold-rolled strip steel production processes improve strength, they also reduce plasticity and toughness, making it prone to distortion and resulting in insufficient surface properties, which makes it difficult to meet the requirements for use in highly corrosive environments.
Using medium carbon steel with specific composition, combined with a six-roll cold rolling mill, gradient quenching-isothermal tempering process and nano-ceramic composite coating technology, through multi-pass rolling, precise tension control, and roll bending and shifting technology, a high-strength nano-ceramic composite coating with gradient structure is formed, which improves the strength and corrosion resistance of the strip steel.
It achieves a balance between high strength and good toughness, significantly reduces bending distortion rate, improves the dimensional stability and wear resistance of strip steel, adapts to highly corrosive environments, and extends product service life.
Smart Images

Figure CN121017246A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application belongs to the technical field of cold-rolled strip steel production, in particular to a high-strength anti-distortion cold-rolled strip steel production process. BACKGROUND
[0002] Cold-rolled strip steel is a thin plate made of hot-rolled strip steel and steel plate as raw materials through processes such as blank preparation, welding, pickling, cold rolling, annealing and finishing at room temperature. Due to its uniform thickness, high plasticity and wide mechanical properties, it is widely used in people's production and life. With the continuous development of industry, higher and higher requirements are put forward for the strength and distortion resistance of cold-rolled strip steel.
[0003] At present, the traditional cold-rolled strip steel production process often leads to a decrease in the plasticity and toughness of the strip steel while improving the strength, and is prone to distortion, affecting the performance of the product. In the heat treatment link, the conventional annealing and quenching and tempering process is difficult to accurately control the internal organization of the strip steel, resulting in uneven performance of the strip steel; in terms of surface treatment, the traditional galvanizing process has limited corrosion resistance and wear resistance, and cannot meet the use requirements in high-corrosion environments.
[0004] Therefore, it is of great practical significance to develop a production process that can improve the strength of cold-rolled strip steel, effectively prevent distortion and improve surface performance. SUMMARY
[0005] Therefore, the technical problem to be solved by the present application is to provide a high-strength anti-distortion cold-rolled strip steel production process to avoid the problems of difficulty in balancing strength and toughness, easy distortion and insufficient surface performance in the previous cold-rolled strip steel production process.
[0006] In order to solve the above technical problems, the present application discloses a high-strength anti-distortion cold-rolled strip steel production process, comprising: Step (1) raw material preparation: selecting medium carbon steel with a carbon content of 0.15%-0.30%, adding manganese 1.0%-1.5%, silicon 0.2%-0.5%, niobium 0.02%-0.05%, vanadium 0.02%-0.04%, controlling the thickness tolerance of hot-rolled strip steel ±0.05mm, width tolerance ±5mm; Step (2) cold rolling process: using a six-roll cold rolling mill set, the working roll diameter is 150-200mm, the intermediate roll diameter is 250-300mm, the support roll diameter is 600-800mm, 5-7 passes are rolled, the first pass reduction rate is 20%-25%, the last pass reduction rate is 3%-5%, the rolling speed is 500-1000m / min, the front tension is 150-200N / mm 2 , the back tension is 120-170N / mm 2 ; Step (3) heat treatment process: sequentially continuous annealing and gradient quenching-isothermal tempering, continuous annealing temperature 750-850℃, holding for 30-60 seconds, protective atmosphere containing hydrogen 5%-10%; gradient quenching adopts double-zone quenching device, high-temperature zone 850℃, medium-temperature zone 700℃, nitrogen gas curtain isolation, heating rate 100℃ / s, strip steel stays in high-temperature zone for 5 seconds and in medium-temperature zone for 3 seconds±0.1 second; isothermal tempering is divided into 300℃, 450℃, 600℃ three temperature zones, temperature transition zone heating slope 50℃ / m; Step (4) surface treatment process: sequentially pickling, hot galvanizing and nano-ceramic composite coating, pickling adopts 15%-20% hydrochloric acid or 10%-15% sulfuric acid, temperature 40-80℃; hot galvanizing temperature 450-480℃; nano-ceramic composite coating is magnetron sputtered after plasma pretreatment, pretreatment vacuum degree 5×10 -3 Pa, argon pressure 1-3Pa, magnetron sputtering adopts alumina-titania composite target, its molar ratio is 7:3, vacuum degree 5×10 -4 Pa, argon-oxygen flow ratio 4:1, sputtering power 2-3kW, strip steel walking speed 10-15m / min.
[0007] According to an embodiment of the present application, in the above gradient quenching-isothermal tempering process, the strip steel thickness direction forms a structure gradient: surface layer 10μm is tempered sorbite, hardness is 28HRC, intermediate layer is tempered troosite, hardness is 32HRC, core is fine needle-shaped tempered martensite, hardness is 38HRC, bending distortion rate≤0.5mm / m.
[0008] According to an embodiment of the present application, the thickness of the above nano-ceramic composite coating is 2-5μm, compactness≥99.5%, 15kHz intermediate frequency pulse power is adopted to suppress arc discharge, after salt spray test (ASTM B117 standard) for 5000 hours, corrosion area is <5%, wear resistance is more than 3 times of traditional galvanized layer.
[0009] According to an embodiment of the present application, in the above cold rolling process, plate shape control is realized by bending roll, roll shifting and segmented roll cooling, cooperating with laser plate shape instrument closed loop adjustment, plate shape precision is controlled within ±0.01mm / m.
[0010] According to an embodiment of the present application, in the above hot galvanizing process, 0.1%-0.3% aluminum and 0.05%-0.1% magnesium are added in zinc liquid, galvanized layer thickness is controlled within 5-20μm, zinc layer adhesion is tested by crosshatch method and reaches 0 level.
[0011] According to an embodiment of the present application, in the above continuous annealing process, nitrogen purity of protective atmosphere≥99.99%, dew point≤-40℃, preventing strip steel surface oxidation to produce iron scale.
[0012] According to an embodiment of the present application, in the pickling process, the stirring speed is 100-200 r / min when mechanical stirring is used, and the ultrasonic frequency is 20-40 kHz when ultrasonic-assisted pickling is used, so as to ensure that the surface roughness Ra of the strip after pickling is less than or equal to 1.0 μm.
[0013] According to an embodiment of the present application, in the two-zone gradient quenching device, the distance between the high-temperature zone and the medium-temperature zone is 500-800 mm, the nitrogen purity of the nitrogen gas curtain is greater than or equal to 99.99%, and the pressure of the nitrogen gas curtain is 0.1-0.2 MPa, so as to ensure that the temperature of the two zones does not interfere with each other.
[0014] According to an embodiment of the present application, in the isothermal tempering process, the length ratio of the three temperature zones is 1:1.5:2, the residence time of the strip in each temperature zone is 20-40 seconds, and the total tempering time is controlled to be 60-120 seconds.
[0015] Compared with the prior art, the present application can achieve the following technical effects: The present application effectively improves the strength and shape accuracy of the strip by selecting the steel type, combining multi-pass rolling in the cold rolling process with precise tension and speed control, and using plate shape control techniques such as bending and roll shifting.
[0016] The gradient quenching-isothermal tempering composite process forms a specific microstructure gradient in the thickness direction of the strip, balances high strength and good toughness, significantly reduces the bending distortion rate, and ensures the dimensional stability of the strip.
[0017] The nano-ceramic composite coating technology greatly improves the corrosion resistance and wear resistance of the strip, enabling it to adapt to high-corrosion environments and prolonging the service life of the product.
[0018] Of course, any product implementing the present application does not necessarily need to achieve all the technical effects described above. BRIEF DESCRIPTION OF DRAWINGS
[0019] The accompanying drawings, which are included to provide a further understanding of the application and are incorporated in and constitute a part of this application, illustrate embodiments of the application and together with the description serve to explain the application. In the drawings: Figure 1 is a production process flow chart of the high-strength anti-distortion cold-rolled strip according to an embodiment of the present application. DETAILED DESCRIPTION
[0020] The embodiments of the present application will be described in detail below with reference to the accompanying drawings and examples, so that the implementation process of how the present application applies technical means to solve technical problems and achieve technical effects can be fully understood and implemented.
[0021] Please refer toFigure 1 , Figure 1 is a high-strength anti-distortion cold-rolled strip steel production process flowchart of the embodiment of the present application.
[0022] As shown in the figure, a high-strength anti-distortion cold-rolled strip steel production process comprises: Step (1) raw material preparation: selecting medium-carbon steel with carbon content of 0.15%-0.30%, adding manganese 1.0%-1.5%, silicon 0.2%-0.5%, niobium 0.02%-0.05%, vanadium 0.02%-0.04%, controlling the thickness tolerance of hot-rolled strip steel ±0.05mm, width tolerance ±5mm; using direct-reading spectrometer to analyze the chemical composition of the raw material, ensuring that the content of each element is within the specified range. Using a metallographic microscope to observe the internal structure of the hot-rolled strip steel, requiring uniform structure, no obvious grain coarsening or inclusion phenomenon. At the same time, the surface of the strip steel is comprehensively inspected to ensure that the surface is flat, without defects such as iron oxide scale, cracks, scratches, etc.
[0023] Step (2) cold rolling process: using a six-roll cold rolling mill, the working roll diameter is 150-200mm, the intermediate roll diameter is 250-300mm, and the support roll diameter is 600-800mm, with 5-7 passes of rolling, the first pass reduction rate is 20%-25%, the last pass reduction rate is 3%-5%, the rolling speed is 500-1000m / min, the front tension is 150-200N / mm 2 , the back tension is 120-170N / mm 2 ; in terms of shape control, the bending roll technology, roll shifting technology and segmented roll cooling technology are combined. The bending roll system adjusts the bending roll force of the working roll in real time according to the plate shape data detected by the laser plate shape instrument, with a range of 50-150kN. The roll shifting system adjusts the transverse distribution of the roll gap by axially moving the intermediate roll, and the roll shifting amount is controlled within ±100mm. The segmented roll cooling system divides the roll into 5 cooling segments, and the cooling water flow of each cooling segment can be independently adjusted, with a flow range of 50-200L / min, to control the thermal crown of the roll. The laser plate shape instrument monitors the plate shape of the strip steel in real time, feeds back the data to the control system, forms a closed-loop control, and ensures that the plate shape precision is controlled within ±0.01mm / m.
[0024] Step (3) heat treatment process: sequentially performing continuous annealing and gradient quenching-isothermal tempering, the continuous annealing temperature is 750-850℃, the holding time is 30-60 seconds, and the protective atmosphere contains 5%-10% hydrogen; the gradient quenching uses a double-zone quenching device, the high-temperature zone is 850℃, the medium-temperature zone is 700℃, the nitrogen gas curtain is isolated, the heating rate is 100℃ / s, the strip steel stays in the high-temperature zone for 5 seconds and in the medium-temperature zone for 3 seconds±0.1 seconds; the isothermal tempering is divided into three temperature zones of 300℃, 450℃ and 600℃, and the heating slope in the temperature transition zone is 50℃ / m; The temperature of the continuous annealing furnace is set to 800℃, and the holding time of the strip in the furnace is 45 seconds. The protective atmosphere is composed of hydrogen and nitrogen, with a hydrogen content of 8% and a nitrogen purity of ≥99.99%, and the dew point is controlled at -45℃. Before entering the annealing furnace, the strip passes through a sealed chamber to prevent external air from entering the furnace. During the annealing process, the furnace temperature is monitored in real time by thermocouples to ensure that the temperature is stable within the set range. After annealing, the strip is cooled by the cooling section at a cooling speed of 50℃ / s until it cools to room temperature.
[0025] The gradient quenching-isothermal tempering process uses a double-zone quenching device, with the high-temperature zone set to 850℃ and the medium-temperature zone set to 700℃. The distance between the two temperature zones is 650mm. The two temperature zones are separated by a nitrogen gas curtain with a purity of ≥99.99% and a pressure of 0.15MPa and a flow rate of 50L / min to prevent temperature interference between the two zones. After entering the high-temperature zone, the strip is heated to 850℃ at a heating rate of 100℃ / s and held at this temperature for 5 seconds. Then, the strip enters the medium-temperature zone and is held at 700℃ for 3 seconds. The isothermal tempering furnace is divided into three temperature zones, 300℃, 450℃, and 600℃, with a length ratio of 1:1.5:2 and a total length of 6m. The strip stays in each temperature zone for 30 seconds, 45 seconds, and 60 seconds, respectively, with a total tempering time of 135 seconds. The heating slope of the temperature transition zone is 50℃ / m to ensure that the strip does not generate excessive thermal stress during temperature changes. During the tempering process, the temperature of each temperature zone is monitored in real time by the temperature sensor in the furnace to ensure that the temperature is controlled within ±5℃ of the set value.
[0026] After the gradient quenching-isothermal tempering process, the strip is tested. The hardness of different positions of the strip is measured by a hardness tester, with a hardness of 28HRC at the surface layer of 10μm, 32HRC at the intermediate layer, and 38HRC at the core. The microstructure of the strip is observed by metallographic analysis, with a tempered sorbite at the surface layer, a tempered troosite at the intermediate layer, and a fine needle-shaped tempered martensite at the core. The bending distortion rate of the strip is detected using a special measuring tool, with a result of 0.4mm / m, meeting the requirement of ≤0.5mm / m.
[0027] Step (4) surface treatment process: acid pickling, hot galvanizing and nano ceramic composite coating are carried out in sequence, acid pickling uses 15%-20% hydrochloric acid or 10%-15% sulfuric acid, temperature 40-80℃; hot galvanizing temperature 450-480℃; nano ceramic composite coating is magnetron sputtered after plasma pretreatment, pretreatment vacuum degree 5×10 -3Pa, argon pressure 1-3 Pa, magnetron sputtering using an aluminum oxide-titanium dioxide composite target with a molar ratio of 7:3, vacuum degree 5x10 -4 Pa, argon-oxygen flow ratio 4:1, sputtering power 2-3 kW, strip speed 10-15 m / min.
[0028] In detail, the pickling process uses 18% hydrochloric acid solution for pickling, and the pickling temperature is controlled at 50°C. During pickling, mechanical stirring is used, with a stirring rate of 150 r / min to improve pickling efficiency. The pickling time is 4 minutes to ensure that the oxide scale on the surface of the strip is completely removed. After pickling, the strip is rinsed in clean water to remove the residual acid on the surface, and then dried. The surface roughness of the pickled strip is measured by a surface roughness meter to ensure that Ra≤1.0 μm.
[0029] The zinc liquid temperature in the hot-dip galvanizing tank of the hot-dip galvanizing process is controlled at 460°C, and 0.2% aluminum and 0.08% magnesium are added to the zinc liquid. After pretreatment, the strip enters the zinc liquid, and by controlling the running speed of the strip and the immersion time in the zinc liquid, the thickness of the zinc plating layer is controlled at 12 μm. After the strip is drawn out of the zinc liquid, the thickness and uniformity of the zinc plating layer are adjusted by air knife wiping, with an air knife pressure of 0.2 MPa. After the zinc plating layer cools and solidifies, the zinc layer adhesion is tested by the grid method, and the test result reaches level 0.
[0030] In the nano ceramic composite plating process, it specifically includes plasma pretreatment and magnetron sputtering. The plasma pretreatment is to send the hot-dip galvanized strip into the vacuum pretreatment cavity, first vacuum the cavity to 5x10⁻³ Pa, then introduce argon with a purity of 99.99% to maintain the pressure in the cavity at 2 Pa. Turn on the plasma spray gun, set the power to 600 W, and pretreat the surface of the strip for 3 minutes to remove oil and impurities on the surface and increase the surface roughness. After pretreatment, the strip enters the magnetron sputtering cavity, and the cavity maintains a vacuum degree of 5x10⁻³ Pa. An Al2O3-TiO2 composite target (molar ratio 7:3) is used for sputtering, and argon-oxygen mixed gas is introduced with a flow ratio of 4:1 and a total flow rate of 50 sccm. The sputtering power is set to 2.5 kW, and the strip speed is 12 m / min. By controlling these parameters, the plating layer thickness reaches 3 μm. During sputtering, a 15 kHz intermediate frequency pulse power is used to suppress arc discharge to ensure the quality of the plating layer. 4
[0031] The nano ceramic composite coating is detected for performance, a metallographic microscope is used to observe the compactness of the coating, and the result is greater than or equal to 99.5%. The salt spray test is carried out according to the ASTM B117 standard, and the corrosion area of the coating is 3% after 5000 hours. The wear resistance of the coating is determined by the Taber wear test, and the result is 3.2 times that of the traditional galvanized layer.
[0032] Preferably, in the hot galvanizing process, 0.1%-0.3% aluminum and 0.05%-0.1% magnesium are added to the zinc liquid, the thickness of the zinc layer is controlled to be 5-20μm, and the adhesion of the zinc layer is tested by the crosshatch method to be 0 level.
[0033] Further, in the gradient quenching two-zone quenching device, the distance between the high-temperature zone and the medium-temperature zone is 500-800mm, the nitrogen purity of the nitrogen gas curtain is greater than or equal to 99.99%, the gas curtain pressure is 0.1-0.2MPa, and the temperature of the two zones is ensured not to interfere.
[0034] In addition, in the isothermal tempering process, the length ratio of the three temperature zones is 1:1.5:2, the residence time of the strip steel in each temperature zone is 20-40 seconds, and the total tempering time is controlled to be 60-120 seconds.
[0035] An X-ray thickness gauge is installed on the cold rolling production line to monitor the thickness of the strip steel in real time, and the measurement accuracy is ±0.01mm. A laser range finder is used to detect the width of the strip steel, and the accuracy is ±1mm. A laser flatness gauge detects the flatness of the strip steel in real time, and transmits the data to the control system to adjust the process parameters in time. At the same time, a high-definition camera is used to monitor the surface of the strip steel online, and surface defects are found and timely alarm.
[0036] The above description shows and describes several preferred embodiments of the present application, but as previously described, it should be understood that the present application is not limited to the forms disclosed herein, and should not be considered as excluding other embodiments, but can be used in various other combinations, modifications and environments, and can be modified within the scope of the inventive concept described herein by the above teaching or related art or knowledge. Any modification and change made by those skilled in the art without departing from the spirit and scope of the present application shall be within the protection scope of the appended claims of the present application.
Claims
1. A high-strength, distortion-resistant cold-rolled strip steel production process, characterized in that, include: Step (1) Raw material preparation: Select medium carbon steel with a carbon content of 0.15%-0.30%, add 1.0%-1.5% manganese, 0.2%-0.5% silicon, 0.02%-0.05% niobium, and 0.02%-0.04% vanadium, and control the thickness tolerance of hot-rolled strip steel to ±0.05mm and the width tolerance to ±5mm; Step (2) Cold rolling process: A six-roll cold rolling mill is used, with a work roll diameter of 150-200mm, an intermediate roll diameter of 250-300mm, and a support roll diameter of 600-800mm. The rolling process involves 5-7 passes, with a first pass reduction of 20%-25% and a last pass reduction of 3%-5%. The rolling speed is 500-1000m / min, the initial tension is 150-200N / mm², and the final tension is 120-170N / mm². 2 ; Step (3) Heat treatment process: Continuous annealing and gradient quenching-isothermal tempering are carried out in sequence. The continuous annealing temperature is 750-850℃, and the holding time is 30-60 seconds. The protective atmosphere contains 5%-10% hydrogen. The gradient quenching adopts a dual-zone quenching device with a high temperature zone of 850℃ and a medium temperature zone of 700℃. Nitrogen gas curtain is used for isolation. The heating rate is 100℃ / s. The strip steel stays in the high temperature zone for 5 seconds and in the medium temperature zone for 3 seconds ± 0.1 seconds. The isothermal tempering is divided into three temperature zones: 300℃, 450℃, and 600℃. The heating slope of the temperature transition zone is 50℃ / m. Step (4) Surface treatment process: Pickling, hot-dip galvanizing, and nano-ceramic composite coating are performed sequentially. Pickling uses 15%-20% hydrochloric acid or 10%-15% sulfuric acid at a temperature of 40-80℃; hot-dip galvanizing temperature is 450-480℃; the nano-ceramic composite coating is pretreated by plasma and then magnetron sputtered with a pretreatment vacuum degree of 5×10⁻⁶. -3 Pa, argon pressure 1-3 Pa, magnetron sputtering using an alumina-titanium dioxide composite target with a molar ratio of 7:3, vacuum degree 5×10 Pa. -4 Pa, argon-oxygen flow ratio 4:1, sputtering power 2-3kW, strip speed 10-15m / min.
2. The high-strength, distortion-resistant cold-rolled strip steel production process according to claim 1, characterized in that, In the gradient quenching-isothermal tempering process, a microstructure gradient is formed in the thickness direction of the strip: the surface 10μm is tempered sorbite with a hardness of 28HRC, the middle layer is tempered troostite with a hardness of 32HRC, and the core is fine acicular tempered martensite with a hardness of 38HRC, with a bending distortion rate ≤0.5mm / m.
3. The high-strength, distortion-resistant cold-rolled strip steel production process according to claim 1, characterized in that, The thickness of the nano-ceramic composite coating is 2-5μm, the density is ≥99.5%, the arc discharge is suppressed by a 15kHz medium frequency pulse power supply, the corrosion area is <5% after 5000 hours of salt spray test (ASTM B117 standard), and the wear resistance is more than 3 times that of traditional zinc coating.
4. The high-strength, distortion-resistant cold-rolled strip steel production process according to claim 1, characterized in that, In the cold rolling process, the shape is controlled by segmented cooling of bending rolls, shifting rolls, and rolling rolls. Combined with closed-loop adjustment by a laser shaper, the shape accuracy is controlled within ±0.01mm / m.
5. The high-strength, distortion-resistant cold-rolled strip steel production process according to claim 1, characterized in that, In the hot-dip galvanizing process, 0.1%-0.3% aluminum and 0.05%-0.1% magnesium are added to the zinc bath, the zinc coating thickness is controlled at 5-20μm, and the zinc coating adhesion reaches level 0 through cross-cut adhesion test.
6. The high-strength, distortion-resistant cold-rolled strip steel production process according to claim 1, characterized in that, In the continuous annealing process, the nitrogen in the protective atmosphere has a purity of ≥99.99% and a dew point of ≤-40℃ to prevent oxidation of the strip surface and the formation of iron oxide scale.
7. The high-strength, distortion-resistant cold-rolled strip steel production process according to claim 1, characterized in that, In the pickling process, when mechanical stirring is used, the stirring rate is 100-200 r / min, and when ultrasonic-assisted pickling is used, the ultrasonic frequency is 20-40 kHz, to ensure that the surface roughness Ra of the strip steel after pickling is ≤1.0 μm.
8. The high-strength, distortion-resistant cold-rolled strip steel production process according to claim 1, characterized in that, In the gradient quenching dual-zone quenching device, the distance between the high-temperature zone and the medium-temperature zone is 500-800mm, the nitrogen purity of the nitrogen curtain is ≥99.99%, and the curtain pressure is 0.1-0.2MPa, to ensure that the temperatures of the two zones do not interfere with each other.
9. The high-strength, distortion-resistant cold-rolled strip steel production process according to claim 1, characterized in that, In the isothermal tempering process, the length ratio of the three temperature zones is 1:1.5:2, the residence time of the strip in each temperature zone is 20-40 seconds, and the total tempering time is controlled at 60-120 seconds.
Citation Information
Cited By
420MPa-grade galvanized low-alloy high-strength steel and production method thereof
CN121951392A
Copper-aluminum composite board and preparation method thereof
CN122209831A